2021
DOI: 10.3389/fped.2021.601492
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound May Reduce Misdiagnosis of Pediatric Intussusception

Abstract: Aim: Intussusception, the most common abdominal emergency in early childhood, is frequently misdiagnosed at initial presentation. The effect of using point-of-care ultrasonography (POCUS) by emergency medicine physicians on pediatric intussusception misdiagnosis rate remains unclear. Here, we summarize outcomes and misdiagnoses before and after training junior and senior physicians on using POCUS for diagnosing intussusception and compared their performance levels.Materials and Methods: This observational coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…To help diagnose appendicitis, intussusception or perform a FAST (focused assessment with sonography in trauma) scan in the setting of pediatric trauma. This is in keeping with the literature, where POCUS has been described in several institutions as a valuable means of providing timely diagnosis of intussusception, in order to avoid delays in treatment and reduce the risk of bowel necrosis [8][9][10] . Several studies have demonstrated 100% sensitivity in detecting intussusception when POCUS is performed by non-radiology clinicians [8][9][10][11] .…”
Section: Accepted Manuscriptsupporting
confidence: 84%
See 1 more Smart Citation
“…To help diagnose appendicitis, intussusception or perform a FAST (focused assessment with sonography in trauma) scan in the setting of pediatric trauma. This is in keeping with the literature, where POCUS has been described in several institutions as a valuable means of providing timely diagnosis of intussusception, in order to avoid delays in treatment and reduce the risk of bowel necrosis [8][9][10] . Several studies have demonstrated 100% sensitivity in detecting intussusception when POCUS is performed by non-radiology clinicians [8][9][10][11] .…”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…[8][9][10] Several studies have demonstrated 100% sensitivity in detecting intussusception when POCUS is performed by non-radiology clinicians. [8][9][10][11] 44.5% (N ¼ 83/186) of respondents had self-perceived competence (from basic to being confident enough to train others) in diagnosing intussusception with POCUS. About 27.4% (N ¼ 51/186) would like to learn POCUS for this purpose.…”
Section: Personal Experience Of Point-of-care Ultrasound In Current P...mentioning
confidence: 99%
“…Ultrasound has a sensitivity of about 98-100% and specificity of almost 98% to diagnose intussusceptions. [6][7][8] In our study, ultrasound helped in almost every case for the diagnosis; and ultrasound-guided hydrostatic reduction as well in the majority of the patients. Hydrostatic reduction is an urgent emergency intervention and should be performed soon after diagnosis with preparation for possible surgical intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Ultrasonography is now a more commonly suggestive and preferable diagnostic modality in addition to plain radiography and contrast enema study. [4][5][6][7][8] If not recognized and treated promptly, intussusception may progress to intestinal ischemia needing a bowel resection. [9] Saline, Barium, or gas enemas are mostly used to reduce uncomplicated intussusceptions, although it has been reported that 10% to 30% of cases eventually need sur-…”
Section: Introductionmentioning
confidence: 99%
“…14 Similarly, it has been estimated that the sensitivity of POCUS for the identification of intussusception is 90% among PEM physicians with focused training in bowel sonography compared with 79% among those without formal training. 8 More recently, Hsiao et al 31 showed that misdiagnosis of intussusception by POCUS decreased from 44% to 13% after the implementation of formal POCUS training; however, misdiagnosis rates improved more among senior compared with junior physicians with less clinical experience. Given the modest sensitivity and specificity among novice reviewers in our study, it is likely that a more focused training curriculum, including image interpretation, is needed for residents and PEM fellows.…”
Section: Discussionmentioning
confidence: 99%